ENHANCING VOCABULARY LEARNING THROUGH VISUAL AND DIGITAL TOOLS IN ENGLISH LANGUAGE TEACHING (SCIENCE TIME JOURNAL, 2026)
Vocabulary is one of the most important components of foreign language learning because learners need words to understand texts, express ideas, participate in communication, and develop all language skills. However, many students find vocabulary learning difficult when it is based only on memorization, translation, and repeated writing. In modern English language teaching, visual and digital tools offer more effective ways to present, practise, and review new words. Pictures, flashcards, real objects, infographics, mind maps, videos, online quizzes, digital flashcards, Padlet, Kahoot, Quizlet, Wordwall, and other platforms can make vocabulary learning more meaningful, memorable, and interactive. This article discusses the importance of vocabulary in language learning, the role of visual materials, the benefits of digital tools, practical classroom activities, and the challenges teachers may face when using technology. It argues that visual and digital tools can improve students’ vocabulary acquisition by increasing motivation, supporting memory, encouraging active participation, and connecting new words with real-life contexts. At the same time, the article emphasizes that these tools should be used purposefully and should always be connected with clear learning objectives.